Alpha-linolenic acid pretreatment alleviates NETs-induced alveolar macrophage pyroptosis by inhibiting pyrin inflammasome activation in a mouse model of sepsis-induced ALI/ARDS - Liu, Chenchen; Zhou, Yu; Tu, Qing; Yao, Liangfang; Li, Jinbao; Yang, Zhongwei (Frontiers in Immunology, 2023)
Background Neutrophil extracellular traps (NETs) can cause acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) by inducing macrophage pyroptosis. The purpose of this study was to find out whether pretreatment of alpha-linolenic acid (ALA) could inhibit NETs-induced macrophage pyroptosis in sepsis-induced ALI/ARDS, as well as to identify which inflammasome is involved in this process. Methods LPS was instilled into the trachea to establish sepsis-induced ALI/ARDS in a mouse model. ​Lung injury was assessed by microscopic examination of lung tissue after hematoxylin and eosin staining, pathology score, and bronchoalveolar lavage fluid (BALF) total protein concentration. The level of NETs in lung tissue was detected by MPO-DNA ELISA. Purified NETs, extracted from peritoneal neutrophils, induced macrophage pyroptosis in vitro. Expression of pyroptosis-related proteins (Cl-caspase-1, Cl-GSDMD, ASC) and IL-1β in the lung tissue and bone marrow-derived macrophages (BMDMs) were determined by western blotting or ELISA. Specks of Pyrin/ASC were examined by confocal immunofluorescence microscopy. Mefv (Pyrin)-/- mice were used to study the role of Pyrin in the process of sepsis-induced ALI/ARDS. Results ALA alleviated LPS-induced lung injury. ALA reduced the level of NETs, pyroptosis-related proteins (Cl-caspase-1, Cl-GSDMD, ASC), and IL-1β in the lung tissue of sepsis mice. In vitro, NETs increased the expression of pyroptosis-related proteins (Cl-caspase-1, Cl-GSDMD, ASC) and IL-1β significantly in BMDMs. Pyrin protein was found to be higher and form the inflammasome with ASC in NETs challenged-BMDMs. Knockout of Mefv (Pyrin) gene fully restored the increased expression of pyroptosis-related proteins (Cl-caspase-1, Cl-GSDMD, ASC) and IL-1β in vitro and in vivo. Lung injury was alleviated significantly in Mefv (Pyrin)-/- mice as well.​ ALA suppresses all the NETs-induced changes as mentioned above. Conclusion Our study is the first to demonstrate Pyrin inflammasome driving NETs-induced macrophage pyroptosis, and ALA may reduce ALI/ARDS by inhibiting the activation of the Pyrin inflammasome-driven macrophage pyroptosis.